Microscopic study on the total number of follicles of ovary in Bangladeshi female cadavers - Qasim, Rubina; Naushaba, Humaira; Ullah, Md Enayet; Hena, Hasna; Khan, Laila Farzana (Update Dental College Journal, 2014)
Context: The ovaries are paired female reproductive and endocrine glands. It is an unique organ in the female body. It undergoes various changes under the influence of hormones which started from prepubertal period and continue up to post menopausal period. Reproductive life span is determined by the histological changes of ovarian follicles. The study was carried out to counting the total number of follicles in relation to age. Study design: Cross sectional, descriptive type of study. Place and period of study: Department of Anatomy, Sir Salimullah Medical College (SSMC), Dhaka from July 2010 to June 2011. Materials: 65 ovaries of Bangladeshi female cadavers age ranging from 5 years to 65 years. Methods: The samples were divided into four different age groups. They were group A or prepubertal group (5-12years), group B or reproductive group (13-45 years), group C or perimenopausal group (46-51years) and group D or postmenopausal group (52-65years). Histological studies were carried out only in right ovary on 24 fresh samples, 6 samples from each group. RESULTS: The mean (±SD) total number of the follicles in the right ovaries were 82.67±2.07, 43.33±8.17, 10.00± 5.47 and 1.17±1.94 per square millimeter in group A, B, C & D respectively. The differences of the mean (±SD) number of the follicles were highly significant (P<0.001) among the all age groups and was significant (P<0.01) when compared between group C with group D. CONCLUSION: Age related changes were observed in the total number of follicles of the ovary. DOI: http://dx.doi.org/10.3329/updcj.v3i1.17979 Update Dent. Coll. j: 2013; 3 (1): 12-17